2023
DOI: 10.1108/ijwbr-07-2022-0026
|View full text |Cite
|
Sign up to set email alerts
|

Examining motivations and challenges of black wine entrepreneurs using the push–pull theory of entrepreneurship

Abstract: Purpose The two major entrepreneurial motivations of being “pushed” or “pulled” to start a business have been frequently explored in the entrepreneurship literature. In the global wine industry, thousands of small entrepreneurial wine businesses are flourishing, but few have been started by Black entrepreneurs. What is missing from the research is an exploration of the motivations of these entrepreneurs and what the industry can do to encourage the entrance of more minority entrepreneurs. The purpose of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The research included both a comprehensive survey questionnaire that garnered more than 100 responses, and more than 40 in-depth, Zoom-based interviews with self-employed Black wine producers, distributors, educators and media. An analysis of the interviews revealed that racism emerged as the foremost challenge for Black wine entrepreneurs, followed consecutively by access to financial capital, sexism, industry experience, distribution, and mental health (Bell, Thach & Fang, 2023). This finding mirrors the result that 78% of survey respondents indicate that racism is a greater challenge in wine than in other industries .…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…The research included both a comprehensive survey questionnaire that garnered more than 100 responses, and more than 40 in-depth, Zoom-based interviews with self-employed Black wine producers, distributors, educators and media. An analysis of the interviews revealed that racism emerged as the foremost challenge for Black wine entrepreneurs, followed consecutively by access to financial capital, sexism, industry experience, distribution, and mental health (Bell, Thach & Fang, 2023). This finding mirrors the result that 78% of survey respondents indicate that racism is a greater challenge in wine than in other industries .…”
Section: Introductionmentioning
confidence: 64%
“…For Black wine business owners, there are a multitude of obstacles that impede success in this seductive industry. Perhaps its unsurprising that the all-encompassing theme of racism was ranked as the foremost challenge among interview subjects, with nearly triple the mentions of the next closest theme of finances/capital (Bell, Thach & Fang, 2023). By definition, systemic racism's tentacles are ubiquitous in the economy and markets.…”
Section: Black Wine Business Ownershipmentioning
confidence: 99%
See 3 more Smart Citations